ImmunoPET imaging of amyloid-beta in a rat model of Alzheimer’s disease with a bispecific, brain-penetrating fusion protein - Bonvicini Gillian; Syvänen Stina; Andersson Ken G.; Haaparanta-Solin Merja; Lopez-Picon Francisco; Sehlin Dag (Springer Science and Business Media {LLC}, 2025)
Background: Hijacking the transferrin receptor (TfR) is an effective strategy to transport amyloid-beta (Aβ) immuno-positron emission tomography (immunoPET) ligands across the blood-brain barrier (BBB). Such ligands are more sensitive and specific than small-molecule ligands at detecting Aβ pathology in mouse models of Alzheimer's disease (AD). This study aimed to determine if this strategy would be as sensitive in rats and to assess how TfR affinity affects BBB transport of bispecific immunoPET radioligands.
Methods: Two affinity variants of the rat TfR antibody, OX26, were chemically conjugated to a F(ab')2 fragment of the anti-Aβ antibody, bapineuzumab (Bapi), to generate two bispecific fusion proteins: OX265-F(ab')2-Bapi and OX2676-F(ab')2-Bapi. Pharmacokinetic analyses were performed 4 h and 70 h post-injection of radioiodinated fusion proteins in wild-type (WT) rats. [124I]I-OX265-F(ab')2-Bapi was administered to TgF344-AD and WT rats for in vivo PET imaging. Ex vivo distribution of injected [124I]I-OX265-F(ab')2-Bapi and Aβ pathology were assessed.
Results: More [125I]I-OX265-F(ab')2-Bapi was taken up into the brain 4 h post-administration than [124I]I-OX2676-F(ab')2-Bapi. [124I]I-OX265-F(ab')2-Bapi PET visualized Aβ pathology with significantly higher signals in the TgF344-AD rats than in the WT littermates without Aβ pathology. The PET signals significantly correlated with Aβ levels in AD animals.
Conclusion: Affinity to TfR affects how efficiently a TfR-targeting bispecific fusion protein will cross the BBB, such that the higher-affinity bispecific fusion protein crossed the BBB more efficiently. Furthermore, bispecific immunoPET imaging of brain Aβ pathology using TfR-mediated transport provides good imaging contrast between TgF344-AD and WT rats, suggesting that this immunoPET strategy has the potential to be translated to higher species.